The Relationship between Emotional Intelligence and Stress Management among Teachers in Secondary School - Apar, Norsyahira; Rodzalan, Shazaitul Azreen (Research in Management of Technology and Business, 2022)
Stress is a common issue yet it is not something that people should ignore. Stress is when someone is feeling overwhelmed and unable to cope with their mental or emotional when they go through difficulties. This research focused on the teachers of secondary school because it has been stated that they had high prevalence of stress symptoms due to problems dealing with students and administrative work. Therefore, the objectives of this research are to measure both the level of Emotional Intelligence (EI) and the stress management of teachers in secondary school. Moreover, this research also aimed to find out the relationship between the EI and stress management of teachers in secondary school. This research used quantitative approach and a survey was conducted by using questionnaire as research instrument. Furthermore, this study found that four dimensions of EI which are self-awareness, self-regulation, motivation and empathy has significant relationship with stress management while social skills does not have significant relationship with the stress management. This research can provide a better understanding for the teachers about how EI skills can help them in stress management. In addition, this research can give awareness to the school administrator on the issue regarding stress of the teachers and they can help those teachers that is struggling with stress management.